Effect of surface functionalization on mechanical properties and decomposition kinetics of high performance polyetherimide/MWCNT nano composites. (November 2016) - Pitchan, Mohan Kumar; Bhowmik, Shantanu; Balachandran, Meera; Abraham, M.
Abstract: In this investigation, Polyetherimide (PEI) reinforced with multi-walled carbon nanotube (MWCNT) using novel melt blending technique. Surface of MWCNTs are modified by acid treatment as well as by plasma treatment. PEI nano composites with 2 wt% treated MWCNT shows about 15% improvement in mechanical properties when compared to unfilled PEI. The thermal decomposition kinetics of PEI/MWCNT nano composites has been critically analyzed by using Coats – Redfern model. The increase in activation energy for thermal degradation by 699 kJ/mol for 2 wt% MWCNT implies improvement in the thermal properties of PEI. Studies under Fourier Transform Infrared Spectroscopy (FTIR) and Transmission Electron Microscopy (TEM) depict significant interfacial adhesion with uniform dispersion of MWCNT in polymer matrix due to surface functionalization. 0.5 wt% chemically modified MWCNT shows typical alignment of MWCNT. There is a significant improvement in mechanical properties and thermal properties for surface functionalized MWCNT reinforced.